Centrifugal separation of irradiated cultures of Escherichia coli cells into viable and nonviable populations. - Schenley, R L (1976)
Incubation of ultraviolet-irradiated Escherichia coli B/r cultures with 0.7% Triton X-100 resulted in a large decrease in turbidity. Under phase-contrast optics, most of the irradiated detergent-treated cells were smaller than normal and of low phase density; only a small percentage were normal or larger than normal and of normal phase density. Irradiated cells not treated with detergent showed fewer pronounced morphological changes. Irradiated cells treated with detergent lost large amounts of proteins and ribonucleic acid, but not of deoxyribonucleic acid. Such cultures could be separated by centrifugation into populations of (i) slowly sedimenting cells consisting of small, phase-light cells of low viability and (ii) large cells of normal phase density and high viability (100%). A similar separation was effected in gamma-irradiated cultures.